Electronic Properties and Vibratational Analysis of Synthesized g-C3N4 nanoparticles using Density Functional Theory - Ayyappan, S.; Nithya, R.; Saranya, M.; Sangeetha, R.K.; Gokila, S. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
In the present work, Polymeric metal free Graphitic carbon nitride (g-C3N4) nano particle was synthesized by thermal pyrolysis method without any additives or surfactants. XRD and SEM micrographs clearly show the formation of hexagonal phase of the as prepared g-CN nanoparticles. Calculated FT-IR, FT-Raman and UV-Vis spectra of the g-CN have been analyzed. HOMO LUMO and density of states of the title compound were calculated by density functional theory. Hyper polarizability of the graphitic carbon nitride was calculated by Hartee Fock and density functional method at 6-31G (d,p) basis set. The Natural bonding orbital of graphitic carbon nitride were analysed.Â